Thermodynamic and Computational Fluid Dynamic Analysis of a Microchannel Heat Sink Device: Use of Nanofluids, Effect of Pin Shape and Inclusion Vortex Generators - Castillo-Del Barrio, E (Taiwan Institute of Chemical Engineers, 2026)
Background: Microchannel designs may enhance the cooling of electronic devices by increasing heat flux, reducing thermal resistance, and promoting uniform temperature distribution. This study analyzes entropy generation and exergy destruction in microchannel heat sinks using computational fluid dynamics, comparing various working fluids and geometries. Methods: The working fluids considered include pure water, a water–ethylene glycol mixture (80:20), and a Newtonian nanofluid (Al2O3/water) with 0.0075 volume fraction. Three geometries, including cylindrical and square pins with and without vortex generators, are analyzed in a Reynolds number range of 200 to 800. The steady-state laminar numerical simulations were performed using ANSYS Fluent. Significant findings : The inclusion of vortex generators reduces total entropy generation across all cases. The water–ethylene glycol mixture leads to a reduction of up to 9.52% compared to pure water, making it the most efficient working fluid tested. In contrast, the nanofluid increases entropy generation by up to 3.44%. Higher Reynolds numbers consistently lead to lower entropy generation and exergy destruction. The study also identifies consistent relationships between the entropy generation number and key dimensionless groups such as Reynolds, Nusselt, and Stanton numbers, supporting the development of simplified engineering correlations. These findings provide clear guidance on the trade-offs between fluid selection and geometric design for thermally efficient microchannel cooling systems. © 2025 Taiwan Institute of Chemical Engineers.